Chip-Scaled Ka-Band Photonic Linearly Chirped Microwave Waveform Generator - Brunetti, Giuseppe; Armenise, Mario N.; Ciminelli, Caterina (Frontiers in Physics, 2022)
Synthetic aperture radar (SAR) systems employ a Linearly Chirped Microwave Waveform Generator (LCMWG) with large time–bandwidth product (TBWP), to provide a wide range resolution. Photonics has now been recognized as a disruptive approach to achieve high performance at bandwidth of few tens of gigahertz, with light and compact architectures, due to the typical photonics benefits, such as electromagnetic interference immunity, small power consumption, small footprint, and high immunity to vibration/shock and radiation. In this article, we report on the photonic generation of a high-frequency LCMW, with a large TBWP (102–103), using a chip-scaled architecture, based on a frequency-tunable optoelectronic oscillator (OEO) and a recirculating phase modulation loop (RPML). A new configuration of the OEO employing an ultrahigh Q-factor resonator has been conceived to allow the oscillator working in Ka band at 40 GHz or even more, with very low phase noise. Key building block of the RPML is a phase modulator driven by an engineered parabolic split waveform. The ultra-large pulse compression rate (PCR) >> 102, together with large signal purity, was also obtained, making the proposed architecture particularly suitable for SAR systems with large range resolution demand, such as Earth surveillance and monitoring.